AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN SENI MUSIK DI SMP NEGERI 3 PADANG PANJANG - Junita Fitri; Indrayuda Indrayuda; Tulus Handra Kadir (SENDRATASIK UNP, 2013)
Abstract The purpose of this research was to describe some causes of why the students of VIII.2 at SMPN 3 Padang Panjang were not involved actively in the classroom activities. The data were in the form of observations on the music learning and interviews with the teacher and students of VIII.2. The data were collected through a literature study, observations, interviews, and documentations. The result of this research has proven that the main cause of why the students of VIII.2 at SMPN 3 Padang Panjang were not involved actively in the classroom activities was the teacher. The teacher could not create a good learning process in which students could participate actively. Besides, the capability of the teacher was also inadequate.   Kata kunci: aktivitas, interaksi, kapabilitas, siswa